Linking Vocabulary Proficiency and Listening Skills: A Correlational Study of Eleventh-Grade Students - Siti Zahratul Jannah; Abdul Gafur Marzuki; Rabaniyah Istiqamah (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study aims to determine the correlation between vocabulary mastery and listening comprehension among Grade XI students at MAN 2 Palu City. This study was motivated by the limited English vocabulary of students, which often affects their ability to accurately understand spoken English. This study uses a quantitative approach with a correlational design to analyze the relationship between the two variables. The research sample consisted of 35 students selected through purposive sampling. Data were collected through vocabulary tests, listening comprehension tests, and supporting questionnaires that measured students' perceptions and attitudes towards vocabulary mastery and listening comprehension in English language learning. Data analysis was performed using SPSS version 26 with normality, linearity, and Pearson Product Moment correlation tests. The results showed a strong and significant positive correlation between students' vocabulary mastery and listening comprehension (r = 0.768, p = 0.000). These findings indicate that students with better vocabulary mastery tend to have higher listening comprehension. In addition, the questionnaire results also show a positive perception of English language learning, which supports student engagement and motivation. Thus, vocabulary mastery plays an important role in improving listening comprehension, and the integration of vocabulary learning into listening activities is recommended to improve students' English learning outcomes.